CCL5 mediates target‐kinase independent resistance to FLT3 inhibitors in FLT3‐ITD‐positive AML. Issue 4 (13th February 2020) - Waldeck, Silvia; Rassner, Michael; Keye, Philip; Follo, Marie; Herchenbach, Dieter; Endres, Cornelia; Charlet, Anne; Andrieux, Geoffroy; Salzer, Ulrich; Boerries, Melanie; Duyster, Justus; von Bubnoff, Nikolas
Abstract : FLT3‐ITD tyrosine kinase inhibitors (TKI) show limited clinical activity in acute myeloid leukemia (AML) due to emerging resistance. TKI resistance is mediated by secondary FLT3‐ITD mutations only in a minority of cases. We hypothesize that the cytokine CCL5 protects AML cells from TKI‐mediated cell death and contributes to treatment resistance. We generated PKC412‐ and sorafenib‐resistant MOLM‐13 cell lines as an in vitro model to study TKI resistance in AML. Increased CCL5 levels were detected in supernatants from PKC412‐resistant cell lines compared to TKI‐sensitive cells. Moreover, CCL5 treatment of TKI‐sensitive cells induced resistance to PKC412. In resistant cell lines with high CCL5 release, we observed a significant downregulation of the CCL5‐receptor CCR5 and CXCR4. In these cell lines, TKI resistance could be partly overcome by addition of the CXCR4‐receptor antagonist plerixafor. Microarray and intracellular flow cytometry analyses revealed increased p‐Akt or p‐Stat5 levels in PKC412‐resistant cell lines releasing high amounts of CCL5. Treatment with the CXCR4 antagonist plerixafor, αCCL5, or CCR5‐targeting siRNA led to a decrease of p‐Akt‐positive cells. Transient transfection of sensitive MOLM‐13 cells with a CCL5‐encoding vector mediated resistance against PKC412 and led to an increase in p‐Akt‐positive and p‐Stat5‐positive cells. Isolated AML blasts from patients treated with PKC412 revealed that CCL5 transcript levels increase significantly at relapse. Taken together, our findings indicate that CCL5 mediates resistance to FLT3‐TKIs in FLT3‐ITD‐mutated AML and could possibly serve as a biomarker to predict drug resistance. Abstract : Increased signaling of the CCL5‐CCR5 pathway can protect FLT3‐ITD + AML cells from cell death mediated by tyrosine kinase inhibitors like midostaurin. Thereby, either increased CCL5 release or upregulation of the CCR5/CXCR4 receptors induces enhanced levels of p‐AKT, p‐STAT5, and Bcl‐2, possibly mediating enhanced survival. Therefore, CCL5 could pave the way for new treatment strategies in FLT3‐ITD + AML patients at relapse.